Two novel KIR3DL1 alleles, 3DL1*0150205 and 3DL1*0150206, identified by full-length DNA sequencing. - Yindom, L; Wang, L; Rowland-Jones, S; Dong, T (2014)
KIR3DL1*0150205 and KIR3DL1*0150206 alleles have five and six mutations, respectively, compared with KIR3DL1*0150201.